Zirconium oxidation on the atomic scale - Hudson, D (2011)
This work was produced as part of a multidisciplinary study of the corrosion of zirconium alloys undertaken by a consortium of universities working in the MUZIC program; Oxford, Manchester and The Open University. The objective of the project as a whole was to further the understanding of the mechanisms of the breakaway oxidation process and to characterise these corrosion processes within a number of fuel rod cladding materials. This thesis describes laser 3D atom probe characterisation of the nano-scale chemical redistribution of oxygen and other solutes that occurs at the metal-oxide interface during corrosion, and a large body of technique development that was required to achieve this goal. The development of the metal-oxide interface of ZIRLO, a Zr-Nb-Sn-Fe-O alloy, is followed by generating 3D atomic scale reconstructions at four different stages of corrosion. The formation of a sub-oxide ZrO layer is seen during pre-transition oxide development. The ZrO interfacial layer is consumed by the rapid formation of oxide after the breakaway transition. After transition the chemistry of the interface is similar to the early pre-transition case, although an oxygen-saturated layer of metal adjacent to the interface formed during corrosion remains. The ZrO interfacial layer (Zr-ZrO-ZrO₂) and the region of oxygen-saturated material ahead of the metal-oxide interface alter the distribution of minor alloying additions such as niobium and iron. The ZrO layer increases the acceptance of niobium into the oxide, which is otherwise seen to be rejected at the Zr-ZrO2 interface along with iron. Niobium is seen to precipitate out of solution as nano-scale particles near the interface after around 100 days of corrosion. This is not seen in the bulk metal matrix of the corroded material due to the absence of other factors driving the process: the stress at the interface and a very high oxygen concentration in the metal ahead of the interface. The nano-scale niobium particles are found to be of a meta-stable composition. Iron is seen to redistribute in the corroded material and can be correlated with the local oxygen concentration. Similarities are seen in the behaviour of solutes within pre-transition ZIRLO and Zircaloy-4 (Zr-Sn-Fe-O). In both cases no redistribution of tin is seen at the metal-oxide interface. A Zr-Nb-Ti alloy with very poor corrosion resistance was also analysed in this way, and the similarities and differences with chemically-similar ZIRLO are discussed. The segregation of solutes to grain boundaries and solute clustering within the matrix are also examined before and after corrosion.